2017
DOI: 10.1063/1.4979799
|View full text |Cite
|
Sign up to set email alerts
|

Note: Energy calibration of a femtosecond photoelectron imaging detector with correction for the ponderomotive shift of atomic ionization energies

Abstract: Femtosecond photoelectron imaging spectroscopy is a powerful technique for following state-resolved molecular transformations in complex coupled potential energy landscapes. To avoid unwanted nonlinear side-effects, the employed laser pulse energies are usually reduced to minimal values. However, the energy calibration of the photoelectron imaging detector is ideally performed using multi-photon above-threshold ionization of suitable atomic species, for which rather high laser intensities are required. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The laser intensity was calibrated by measuring the energy shift of the non-resonant ATI peaks of Xe; for further details, please see Refs. [25] and. [26] In our measurement, the laser polarization was parallel to the detector of velocity map imaging (VMI).…”
Section: Methodsmentioning
confidence: 99%
“…The laser intensity was calibrated by measuring the energy shift of the non-resonant ATI peaks of Xe; for further details, please see Refs. [25] and. [26] In our measurement, the laser polarization was parallel to the detector of velocity map imaging (VMI).…”
Section: Methodsmentioning
confidence: 99%
“…In the earlier studies, it has been demonstrated that intensity is a useful knob to shift the position of ATI peak in the energy domain due to the pondermotive energy shift. [44,45] Therefore, the Coulomb effect can be compared between ATI peaks with very close energies by changing laser intensity slightly. We first show how the ATI peaks are shifted in the energy domain by varying the laser intensity from 2.6 × 10 13 W/cm 2 to 8.4 × 10 13 W/cm 2 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For extracting the electron momentum distribution, each measured image is separated into a left and a right part along the polarization and the Abel inversion is performed by using the Basex method [46]. The intensity calibration for both w and 2 w lasers is given by measuring the Stark shift of the electron energy spectra of xenon [47,48].…”
Section: Methodsmentioning
confidence: 99%